The Influence of Instagram and Brand Image on College Enrolling Interest at Universitas Muhammadiyah Jakarta - Fauzalia, Dian; El Adawiyah, Sa'diyah; Patrianti, Tria; Swarnawati, Aminah (Kalijaga Journal of Communication, 2024)
The purpose of this study was to measure the influence of Instagram and brand image on interest in enrolling in college at Universitas Muhammadiyah Jakarta partially and simultaneously. This research approach uses quantitative research. This study used proportional stratified random sampling with 239 student respondents at SMAS Muhammadiyah 8 Ciputat and SMAN 8 South Tangerang City. The data collection technique was carried out using a questionnaire. The data analysis technique used multiple linear regression tests, namely the F and T-tests. This study found that Instagram and brand image positively and significantly affect interest in enrolling in college at the Universitas Muhammadiyah Jakarta, both partially and simultaneously. In conclusion, all hypotheses are accepted. Kata Kunci: komunikasi bisnis, instagram, citra merek, minat, mendaftar kuliah